(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article presents modern data on morphological changes in the heart under the influence of carbon monoxide. Carbon monoxide induces hypoxic damage to the myocardium, accompanied by disturbances in the structural organization of cardiomyocytes and microcirculation. Mitochondrial destruction, sarcoplasmic swelling, myofibril fragmentation, and stromal edema are observed. The degree of morphological disorders correlates with the duration and concentration of carbon monoxide exposure. Experimental and clinical findings provide a basis for further studies of the mechanisms of the toxic cardiomyopathic effect of carbon monoxide.